Analisis Pengelolaan Anggaran Pendapatan Dan Belanja Lembang Dilembang Ma’dong Kecamatan Denpina Kabupaten Toraja Utara - Lusiana Tandi; Adriana Madya Marampa; Elisabet Pali (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This research aims to analyze the Management of the Revenue and Expenditure Budget of the Lembang Ma'dong Fund. To achieve this goal, a qualitative descriptive research method was used. Based on the results of data analysis and discussion regarding the Lembang Ma'dong Fund Revenue and Expenditure Budget Management Analysis, it has been implemented in accordance with the five indicators specified in Minister of Home Affairs Regulation Number 113 of 2014, namely planning, implementation, administration, reporting and accountability. The results of the researchers' findings show that planning involved community participation through village meetings. The implementation uses the principles of self-management and is cash-intensive. In the administration stage, namely in the form of accounting for income and expenses to interested parties. At the reporting stage, it is carried out according to a predetermined time schedule and at the accountability stage, it is always reported in accordance with requirements and on time.